Effects of norgestomet on follicular developments and hormonal profiles during dioestrus and proestrus of oestrous cycle in crossbred cows - AROSH, A JOE; KATHIRESAN, D; SUBRAMANIAN, A; DEVANATHAN, T G (The Indian Journal of Animal Sciences, 2014)
The influence of norgestomet on the secretory patterns of progesterone, oestradiol and luteinizing hormone during dioestrus and proestrus of oestrous cycle were studied in 12 crossbred cows. In all the cows, the oestrus was initially synchronized by 2 intramuscular injections of prostaglandin F2 alpha (PGF2 Î±) at 12 days apart. At oestrus the cows wereÂ divided m to groups 1 and 2. In group 1, the norgestomet implant was implanted at day 9 (dioestrus) of the oestrous cycle, whereas in group 2, it was implanted on day 18 (proestrus) of the oestrous cycle. The onset of oestrus and LH surge were significantly (P<0.01) earlier in group 2 than in 1. Norgestomet during dioestrus has no influence on the secretory patterns of the progesterone oestradiol and luteinizing hormone, whereas, during proestrus, increased the secretory patterns of luteinizing hormone and oestradiol.